Toward an Ecological Understanding of Transnational Chinese Language Teachers’ Professional Wellbeing in the United Kingdom - Wang, Isobel Kai-Hui (Frontiers in Psychology, 2022)
Given the lack of reports of Chinese language teachers' wellbeing in the literature, this study aims to investigate the professional wellbeing of eight teachers of Chinese as a foreign language in the UK based on in-depth, semi-structured qualitative interviews. Interview data provided a rich picture of the rewarding aspects and challenges that they experienced in their professional lives. The main findings revealed the complex interplay of their professional wellbeing and different levels of ecology (i.e., cultural, institutional, classroom, and personal). The study also identified the specific strategies that the teachers deployed for (1) coping with work-related stress and for (2) maintaining wellbeing alongside professional productivity. The paper calls for further research to apply a close-up lens to the wellbeing of foreign language teachers across timescales. The implications for transnational language teachers’ mentoring interventions are discussed.